The Effect of C / N Ratio and Pretreatment in Making Biogas from Tea Waste and Cow Manure in Liquid State Anaerobic Co-Digestion - Ghalih Hakiki Kavisa; Nurlita Sari; Hashfi Hawali Abdul Matin; Budiyono Budiyono (Diponegoro University, 2020)
Energy problems in Indonesia are issues that are not easy to solve. If the energy needs dominated by BBM continue to increase without any changes in the pattern of energy use, then Indonesia's sustainability and energy security will be disrupted. Therefore, Indonesia really needs alternative energy. Biogas is an alternative energy produced from the anaerobic degradation of organic compounds and can be a substitute for natural gas and fossil fuels. Solid tea waste can be used as a substrate from anaerobic co-digestion biogas production with cow dung. In general, the purpose of this study is to produce biogas from tea pulp and cow manure by anaerobic co-digestion and have a specific purpose, namely (i) Assessing the effect of pretreatment on the yield of biogas produced, (ii) Assessing the effect of pH on yield of biogas, (ii) Assessing the effect of the value of the C / N ratio on the yield of the biogas produced. This research was conducted by making variations in treatment including physical pretreatment with and without grinding (± 1 mm), biological pretreatment with and without addition of 5% v / v microbial consortium, pH controlled (addition of buffer) and uncontrolled, and ratio of C: N waste solid tea (25 and 30). The biogas formation process is carried out for 2 months at room temperature with the quantitative response test results in the form of biogas volume every 2 days. Biogas production in pretreatment tea grounds gives better results than without pretreatment. Optimum biogas production is obtained at a C: N 30 ratio. Comparison of C: N substrate will affect the growth of microorganisms, the microbes that play an anaerobic process need nutrients to grow and develop, in the form of carbon and nitrogen. The highest biogas accumulation produced was 73,167 ml / gr TS on variable C / N 30 ratio, NaOH pretreatment, microbial consortium and smooth size of tea waste that used.